Characterization of biodiesel as a fuel in a compression ignition (CI) engine with additives - Mohd Hafizil, Mat Yasin (2012)
Compression ignition engines have been used widely in the transportation sector and power generation for the decades. These engines are less fuel consumed with higher brake thermal efficiency. However, compression ignition engines produce higher pollution in NOx and PM emission as well as cause several negative drawbacks to the environment. Most countries in the world have regulated several regulations to reduce the emission from the engines. Other than that, the introduction of biodiesel in the engines is beneficial and proven to reduce the emission significantly. However, biodiesel has higher density and viscosity with lower heating value as compared to mineral diesel. Fuel additives are among other methods that proven to modify the properties of biodiesel to be comparable with mineral diesel without doing any engine modification. Although fuel additives’ ability to reduce harmful emissions is well known in the literature, the mechanism for these additives is not well understood when operated in the four-stroke, four-cylinder diesel engines. Two alcohol-based additives, methanol and ethanol were diluted with B 20 blend (20% biodiesel + 80% mineral diesel) with the formulation of 5% by volume. The test fuels; mineral diesel, B100 (palm-diesel), B20 blend and B20-alcohol blends (B20 E5 and B20 M5) were investigated on a Mitsubishi 4D68 four stroke, four-cylinder water-cooled diesel engine incorporating sensors for in-cylinder pressure measurement and thermocouples. There were two operating modes dealing with these fuels, which the first mode been conducted on increasing engine speeds at 50% throttle position. While as for the second mode, these fuels were operated at three different engine loads, 0.05 MPa, 0.4 MPa and 0.7 MPa with the engine constant speed of 2500 rpm. The effect of test fuels on brake power, brake specific fuel consumption (BSFC), brake thermal efficiency (BTE), combustion (in-cylinder pressure, rate of heat release, cylinder temperature) and NOx, NO, CO and CO2 emissions were investigated. Results found that the performance of diesel engine improved with the use of alcohol (ethanol and methanol) in the B20 blends especially in comparison to mineral diesel, B100 and B20. Overall, the results indicated that when compared to mineral diesel, B100, B20, B20 E5 and B20 M5 have higher brake thermal efficiency. The use of alcohol as a fuel additive in the B20 blend has improved the combustion characteristics when the loads were applied to the engine. Besides, the exhaust emission for the B20 E5 and B20 M5 were fairly reduced when compared to mineral diesel.